Upaya Penanganan ESKA Berbasis Sektor Daring di Indonesia: (Studi Kasus Kerja Sama Pemerintah dan End Child Prostitution, Child Pornography, and Trafficking of Children for Sexual Purposes 2021–2024) - Angelica Margaret Sitorus; Roberto Octavianus Cornelis Seba; Christian H.J de Fretes (Journal of Innovative and Creativity, 2025)
Online commercial sexual exploitation of children (CSEC) is growing alongside advances in digital technology, requiring strong collaboration between the Indonesian government and non-governmental organizations such as ECPAT Indonesia. Although the government has established various regulations, including the Child Protection Law, the Electronic Information and Transactions Law, and ratified the UN Optional Protocol, the dynamics of cybercrime demand more adaptive handling strategies. This study uses a descriptive qualitative method through a literature review of government documents, international agency reports, and academic publications to analyze the form and effectiveness of government-ECPAT collaboration in the 2021-2024 period. The results show that cooperation has been realized through law enforcement training, public awareness campaigns, regulatory drafting, joint research, and strengthening of case reporting mechanisms, despite challenges such as low reporting rates, the complexity of tracking anonymous perpetrators, digital literacy gaps, and limited assistance services in rural areas. These findings emphasize the importance of continuous synergy among actors to strengthen child protection in the digital space and optimize comprehensive prevention and handling of ESKA